1978
DOI: 10.1002/hlca.19780610425
|View full text |Cite
|
Sign up to set email alerts
|

Enamines I. Vinyl Amine, a Theoretical Study of its Structure, electrostatic potential, and proton affinity

Abstract: SummaryThe structure of vinyl amine and its reactivity towards a proton is studied by the PRDDO SCF MO method. The equilibrium structure is found to be non-planar and barriers to inversion-and rotation-dominated processes are calculated. Proton addition to vinyl amine, as a model of enamine protonation, is examined by means of electrostatic molecular potentials and C-versus N-proton affinities.1. Introduction. -Enamines are readily accessible, highly reactive, and thus synthetically useful intermediates [ 11 [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The three-fold rotational potential is found to entail a barrier of 11.1 kJ/mol with a rotational constant at 271.5 GHz. These values are in excellent agreement with previously reported theoretical predictions [35].…”
supporting
confidence: 82%
See 2 more Smart Citations
“…The three-fold rotational potential is found to entail a barrier of 11.1 kJ/mol with a rotational constant at 271.5 GHz. These values are in excellent agreement with previously reported theoretical predictions [35].…”
supporting
confidence: 82%
“…The experimental results suggest a pyramidal nitrogen for EA. Earlier results [34,35], and a microwave spectroscopic analysis [12] suggested that EA is non-planar. Radom et al [28] and Manocha et al [23] predicted that the gauche conformer is more stable than the trans conformer.…”
Section: The Molecular Structure Of Ethylaminementioning
confidence: 99%
See 1 more Smart Citation
“…Müller and Brown (8), using a semi-empirical method PRDDO (partial retention of diatomic differential overlap), calculated a nonplanar geometry and investigated some aspects of the inversion and torsion motion of vinylamine. Meyer (7), using a flexible molecular model and the results of Müller and Brown (8), examined several possible pathways of the inversion motion.…”
Section: Introductionmentioning
confidence: 99%
“…They characterized the microwave and infrared spectra of VA and EI two isomers, E-and Z-ethyleneimine in a temperature range from 150 to 900 °C and suggested a non-planar structure of vinylamine (CH 2 =CHNH 2 ) [1,2]. Moreover, theoretical studies on VA structure produced the same result [16,18,20,[56][57][58][59][60]. Traeger et.…”
Section: Introductionmentioning
confidence: 87%